Frost Quakes: Crack Formation by Thermal Stress. Issue 9 (18th September 2020) - Okkonen, J.; Neupauer, R. M.; Kozlovskaya, E.; Afonin, N.; Moisio, K.; Taewook, K.; Muurinen, E.
Abstract: Fractures in frozen soils (frost quakes) can cause damage to buildings and other infrastructure, but their formation mechanisms remain poorly understood. A methodology was developed to assess thermal stress on soil due to changes in climate and weather conditions and to investigate the connection between thermal stress and frost quakes in central Finland due to brittle fracturing in uppermost soils. A hydrological model was used to simulate snow accumulation and melt, and a soil temperature model was used to simulate soil temperature at different depths beneath the snow pack. The results of modeling, together with measurements of air temperature, snow cover thickness, and soil temperature, were used to calculate temporal variations in thermal stress in soil. We show that frost quakes occur when thermal stress caused by a rapid decrease in temperature exceeds fracture toughness and strength of the soil‐ice mixture. We compared calculated thermal stress on soil, critical stress intensity factor, and a seismogram recorded in a suburban region in central Finland. Our results suggest that this methodology can be used to predict thermal stresses on soil and identify stress values that may lead to fractures of frozen soils, that is, frost quakes. Key Points: We present a new method to assess thermal stress on frozen soil Frost quakes and soil cracks may occur if thermal stress exceeds fracture toughness and strength of soil‐ice mixture Rapid decrease of air and soil temperature causes frost quakes and soil cracks